The relationship between lower-body maximum strength and swim start performance in youth elite swimmers - Zebura, K.; Fuhrmann, S.; Mathy, A.; Triska, C.; Wirth, K. (Journal of Applied Sports Sciences, 2023)
Swimmers reach the highest accelerations during starts. These are initiated by a high amount of force produced by the lower limbs in a short amount of time. It is established in senior athletes that there is a relationship between lower-body maximum strength and swim start performance. The aim of this study was to investigate the relationship between lower-body maximum strength and swim start performance up to 5 and 15 m in elite youth swimmers. Twenty-two (10 females, 12 males) well-trained adolescent swimmers executed a one repetition maximum (1RM) back squat test, a counter movement jump (CMJ), a squat jump (SJ) test, and two trials of a swim start following a freestyle sprint up to 15 m. Bivariate Pearson correlation analyses were used to assess the relationship between strength and jumping performance and start performances up to 5 and 15 m. The level of signifi cance was set at p < .05. Strength and jumping performance explained 55-73% of the variance in start performance up to 5 and 15 m. Strong correlations were found between re sulting forces on the block and times to 5 and 15 m as well as between 1RM back squat test, CMJ, and SJ and times to 5 and 15 m (all between r = -.75 and r = -.86; p < .01). This study demonstrates that strength parameters of the lower limbs aff ect jumping performance off the block in swimming. Therefore, these parameters are usable predictor variables in assessing start performance up to 5 and 15 m in swimmers.